Tradisi Hidangan Olahan Asal Bulus (Trionyx cartilaginous) dan Analisis Nilai Gizinya (TRADITION AND SOCIAL CULTURES OF MEAL AND NUTRITIVE VALUES OF FOODSTUFFS ORIGINATED FROM FRESH WATER TURTLE (Trionyx cartilagineus)) - Arka, Ida Bagus (Jurnal Veteriner; Vol 1 No 1 (2000), 2016)
Tradisi Hidangan Olahan Asal Bulus ( Trionyx cartilaginous ) dan Analisis Nilai Gizinya   (TRADITION AND SOCIAL CULTURES OF MEAL AND NUTRITIVE VALUES OF FOODSTUFFS ORIGINATED FROM FRESH WATER TURTLE (Trionyx cartilagineus))
Keywords: Traditions and social cultures, meal preparations, fresh water turtle, nutritive values